2018
DOI: 10.1038/s41467-018-06712-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based redesign of docking domain interactions modulates the product spectrum of a rhabdopeptide-synthesizing NRPS

Abstract: Several peptides in clinical use are derived from non-ribosomal peptide synthetases (NRPS). In these systems multiple NRPS subunits interact with each other in a specific linear order mediated by specific docking domains (DDs), whose structures are not known yet, to synthesize well-defined peptide products. In contrast to classical NRPSs, single-module NRPS subunits responsible for the generation of rhabdopeptide/xenortide-like peptides (RXPs) can act in different order depending on subunit stoichiometry there… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 44 publications
0
80
0
9
Order By: Relevance
“…An alignment of the intermodule docking motifs revealed that the first 45 amino acids of the N‐terminal NRPS docking motif (Ndd) on VatN, VatQ, and VatS are 100 % identical, and that the final six residues of the C‐terminal dd (Cdd) on VatM and VatP are identical as well. Sequence alignment of these dd matches previously structurally characterized β‐αββαα type dds . Generally, since residues 24–29 on the β 2 sheet of the N‐terminal NRPS dd confer interaction with the terminal 5–6 residues of the “β 3 ” sheet of the upstream C‐terminal dd, we theorized that there is no selective preference by the upstream C‐terminal VatM/P dds to downstream N‐terminal VatN/Q/S dds.…”
Section: Figurementioning
confidence: 52%
See 2 more Smart Citations
“…An alignment of the intermodule docking motifs revealed that the first 45 amino acids of the N‐terminal NRPS docking motif (Ndd) on VatN, VatQ, and VatS are 100 % identical, and that the final six residues of the C‐terminal dd (Cdd) on VatM and VatP are identical as well. Sequence alignment of these dd matches previously structurally characterized β‐αββαα type dds . Generally, since residues 24–29 on the β 2 sheet of the N‐terminal NRPS dd confer interaction with the terminal 5–6 residues of the “β 3 ” sheet of the upstream C‐terminal dd, we theorized that there is no selective preference by the upstream C‐terminal VatM/P dds to downstream N‐terminal VatN/Q/S dds.…”
Section: Figurementioning
confidence: 52%
“…The interface between modules occurs via interacting type I or II docking domains (dd) between PKSs and communication (COM) domains between some NRPS modules . A third type of structurally distinct docking interaction between combinations of PKS and/or NRPS modules was characterized in tubulysin and rhabdopeptide/xenorpeptide (RXP) biosynthesis, and are referred to here as (C‐terminus‐N‐terminus) β‐αββαα type domains . We used a bioactivity‐ and reactivity‐guided approach to characterize six new lipopeptides and their biosynthetic pathway from the benthic cyanobacterium Moorea producens ASI6Jul14‐2.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The potential acceptor domain, based on sequence homology of conserved residues to C-terminal communication-mediating donor domains (COM), was found at the NcpB4 PCP domain second helix, encompassing conserved serine residue within potential binding sequence [31]. Moreover, this communication-mediating domain may putatively bind to C-terminus of NcpB3 and NcpB4 condensation (C) domains based on conserved motif LLEGIV, found by sequence homology to last five amino-acids of C-terminal docking domains residues, key for their interactions [32]. Within the same β-hairpin, a group of charged residues (ExxxxxKxR) putatively determines the binding affinity of the N-terminal domain [33].…”
Section: Non-ribosomal Peptide Synthetase (Nrps) Gene Cluster Of Nostmentioning
confidence: 99%
“…64 By manipulation of these regions, examples of combinatorial clusters have been generated 65,66 or re-designed to modulate products of single-module NRPS systems. 67 DDs ensure the correct PKS assembly into a functional enzyme. Studies on virginiamycin biosynthesis show that the DDs are essential for the correct assembly of the enzymatic complex and nally for the communication between the KS and ACP domains.…”
Section: Multi-module Exchangementioning
confidence: 99%